PENINGKATAN PEMAHAMAN KONSEP DAN AKTIVITAS BELAJAR FISIKA DENGAN MENGGUNAKAN ASSESMEN KINERJA BERBASIS INQUIRY DI SMA NEGERI 2 PLUS SIPIROK TAHUN PELAJARAN 2018/2019 - Elisa Hanif; Himsar Himsar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
This research is a classroom action research that aims to increase understanding of concepts and learning activities through inquiry-based performance assessment. This study consisted of 2 cycles conducted in class X-2 of SMA Negeri 2 Sipirok, South Tapanuli Regency with a total of 33 students. The characteristics of this class have activeness and low learning outcomes compared to other X classes. The indicator of success for student activity is at least 75%, and the indicator of classical learning outcomes is at least 85% of the number of students who take the test. During the study showed an increase in student activity and learning outcomes from cycle I to cycle II. in the first cycle, the average value of understanding the concept of 71.23 with 64.56% completeness, because it is less than 75%, it has not been said to be completed classically. In the second cycle, the average value of understanding the concept of 82.03 with 87.52% completeness, because more than 75%, has been said to be completed classically. in the first cycle, the average value of learning activities was 65.22 with 52.56% completeness, because it was less than 75%, so it was not yet classically complete. In the second cycle, the average value of learning activities is 80.65 with the completeness of 84.23%, because more than 75%, has been said to be completed classically. From the results of the study, it can be concluded that the application of inquiry-based performance assessment can improve the understanding of concepts and physics learning activities in class X-2 students of SMA Negeri 2 Sipirok.